Pembukuan Usaha Mewujudkan UMKM Naik Kelas (Kolaborasi UMKM Indonesia dan Malaysia) - Irawan Irawan; Ari Irawan (Jurnal Pengabdian Masyarakat Akademisi, 2022)
The main problem of SMEs that is seen today is the low access to capital which results in a very wide gap between small, medium, and large businesses. This phenomenon is related to the lack of understanding of the bookkeeping of business financial statements that are not neatly and completely organized, which is an obstacle in realizing SMEs to upgrade. This can weaken competitiveness and adaptation in the face of the era of digitalization and globalization of trade. The importance of this service is carried out in order to realize the foundation of SMEs to upgrade on the pillars of SME financial bookkeeping which is considered very important in ordering the administration and financial transactions of the business so that it can become an even better access to SME capital. The service method is carried out by means of lectures and discussions related to MSME bookkeeping through virtual meeting media (Zoom meeting). The results of this service can open the insights and knowledge of participants in arranging the bookkeeping of their business financial statements. The first knowledge that can be formed begins with recording business transactions formatted into accounting journals and posting financial accounts. The second knowledge is the increasing understanding of participants in preparing business financial statements that are in accordance with the standards (SAK-EMKM). Finally, participants' knowledge in assessing prospects and performance of business results can be the basis for decision making. The action plan of this activity can certainly be a stimulus for business actors in realizing SMEs to upgrade